2018
DOI: 10.1186/s12960-018-0307-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with retention intentions among Isibindi child and youth care workers in South Africa: results from a national survey

Abstract: BackgroundChild and youth care workers (CYCWs) are a crucial and growing component of South Africa’s national response to HIV and AIDS and other issues affecting children and families. CYCWs use the community-centred Isibindi model of care to reach the most vulnerable with key services including psychosocial, health, economic and education support. Like others in similar professions, they may be at risk for occupational challenges affecting retention.MethodsThis study uses data from the first nationally repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…The desire to make a difference in vulnerable young people lives was found to be key driver for career choice by the CYCWs. The research findings are in agreement with Thurman et al (2018) whereby the respondents indicated that wanting to help children or the community was their primary motivator for CYCWs.…”
Section: Discussion Of Research Findings On the Resilience Of Cycwssupporting
confidence: 86%
“…The desire to make a difference in vulnerable young people lives was found to be key driver for career choice by the CYCWs. The research findings are in agreement with Thurman et al (2018) whereby the respondents indicated that wanting to help children or the community was their primary motivator for CYCWs.…”
Section: Discussion Of Research Findings On the Resilience Of Cycwssupporting
confidence: 86%
“…It also doubly penalises doctors in rural areas as they are more likely to be overworked and less likely to access such training opportunities. This experience mirrors that in other nations [32][33][34]. PLOS GLOBAL PUBLIC HEALTH…”
Section: Discussionsupporting
confidence: 63%
“…Between 2013 and 2018, the program trained community members to provide daily practical support and assistance to more than 1.3 million children (DSD, 2019a;DSD & NACCW, 2014;Jamieson, 2013). Research showed that it also increased participants' access to social grants, material assistance, and family support (Kvalsvig & Taylor, 2015;Thurman et al, 2013;Visser et al, 2015). However, these gains aside:…”
Section: Professional Issuesmentioning
confidence: 99%